Rectus muscle diastasis in Italian women: determinants of disease severity, and associated disorders - Sartori, Alberto; Tfaily, Ahmad; Botteri, Emanuele; Andreuccetti, Jacopo; Lauro, Enrico; Caliskan, Gulser; Verlato, Giuseppe; Di Leo, Alberto (Frontiers in Surgery, 2024)
Purpose: Diastasis of rectus abdominis (DRA) refers to a separation of the rectus abdominis from the linea alba, which is common in the female population during pregnancy and in the postpartum period. The present study aimed at investigating DRA severity, risk factors and associated disorders.In the present cross-sectional study, a web-based questionnaire was addressed to the 23,000 members of the Women's Diastasis Association. The questionnaire comprised three parts, dedicated respectively to diastasis characteristics, possible risk factors, and related disorders. Faecal and urinary incontinences were assessed using the Wexner and ICIQ-SF score, respectively. Risk factors for diastasis severity (<3, 3-5, >5 cm) were evaluated by a multinomial regression model.Results: 4629 women with a mean age (SD) of 39.8 (6.5) years and a median BMI of 23.7 Kg/m 2 (range 16.0-40.0) responded to the questionnaire. Proportion of DRA>5 cm increased from 22.8% in norm weight women to 44.0% in severely obese women, and from 10.0% in nulliparous women to 39.3% in women with >3 pregnancies. These associations were confirmed in multivariable analysis.DRA severity was associated with the risk of abdominal hernia and pelvic prolapse, whose prevalence more than doubled from women with DRA<3 cm (31.6% and 9.7%, respectively) to women with DRA>5 cm (68.2% and 20.2%). In addition, most patients reported postural pain and urinary incontinence, whose frequency increased with DRA severity.The present study confirmed that DRA severity increases with increasing BMI and number of pregnancies. Larger separation between rectal muscles was associated with increased risk of pain/discomfort, urinary incontinence, abdominal hernia and pelvic prolapse. Prospective studies are needed to better evaluate risk factors.